Cosplay – znaczenie fenomenu w relacjach uczestniczek - Wrona, Daria (Studia Edukacyjne, 2020)
Wrona Daria, Cosplay – znaczenie fenomenu w relacjach uczestniczek [Cosplay – the Significance of the Phenomenon in Female Participants’ Accounts]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 385-399. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.21 Cosplay is a poorly understood phenomenon related to popular culture. Currently, however, it is slowly attracting the interest of an increasing number of fields of science, such as sociology, psychology or pedagogy. The following article will present the theoretical foundations and research on the role of cosplay in the life of female cosplayers. Focusing on the subjects, I touched upon the issues of interpersonal interactions, interests and skills, social perception of cosplay, problems related to the preparation of costumes, and the impact of cosplay on identity development.